PEMANFAATAN DAUN SALAM (Eugenia polyantha) SEBAGAI OBAT HERBAL DAN REMPAH PENYEDAP MAKANAN - Kun Harismah (WARTA LPM, 2016)
Eugenia polyantha, one of Indonesian medicine plant, often used in society as traditional medicine and also Indonesian culinary additives. Daun salam is called Indonesian bay-leaf, the leaves contain only tiny amounts of an essential oil 0.2%. As main components, eugenol, methyl chavicol, and citral have been identified. Thus application to used of Eugenia polyantha have done. The aim of the present work was the application of Eugenia polyantha for food and health in the community area of Keraton Surakarta. The results indicated that Eugenia polyantha is of particular interest, since it may be an alternative way to carry out of food flavor simultanous as herbal medicine.